Definition of wind blowers for vehicles testing at chassis-dyno facilities using a CFD approach. (August 2017) - Broatch, A.; Margot, X.; Gil, A.; Galindo, E.; Soler, R.
Highlights: New RDE testing facilities have to reproduce vehicle real on-road conditions. Test cell design must guarantee realistic cooling of the different vehicle components. CFD methodology used to provide guidelines for definition of airflow supply system. Distance between nozzle outlet and car front has greater impact than blower section. On-road conditions can be best reproduced with blower outlet at 1 m from vehicle. Abstract: The need to increase measurement accuracy of fuel consumption and pollutant emissions in vehicles is forcing the market to develop chassis-dyno test cells that reproduce on-road conditions realistically. Air-cooling is key to vehicle performance. It is therefore critical that the design of a test cell guarantees realistic cooling of all vehicle components, as important errors in fuel consumption and emissions measurements may otherwise arise. In a test-room, a blower placed in front of the vehicle supplies the cooling air. While there are some guidelines in the literature for the selection of fans required for emissions measurements for standard driving cycles, the information for designing the air supply system for specific tests in other areas is scarce. New Real Driving Emissions (RDE) legislation will force manufacturers to perform on-road measurements of pollutants. This represents a significant challenge due to the variability of conditions coming from non-controlled parameters. In order to optimize vehicles, different tests are performed in cells equipped with a chassis-dyno where the on-road flow field around the vehicle is reproduced as closely as possible. This work provides some guidelines for the definition of the airflow supply system of chassis-dyno facilities for vehicle optimization tests, based on a CFD analysis of the flow characteristics around the vehicle. By comparison with the solution obtained for a vehicle in real road driving conditions, the exit section of the blower and the distance between the blower exit and the car that best reproduce realistic on-road flow conditions in a test room are determined.